Behaviour change: extralegal, apolitical, scientistic? - Magdalena Małecka; Robert Lepenies (Edward Elgar Publishing, 2021)
Behavioural change has become a core issue of public policy. Behavioural instruments such as ‘nudging’ apply insights from behavioural economics and behavioural sciences, psychology and neurosciences across a broad range of policy areas. Behavioural insights teams and networks facilitate the global spread of behavioural public policies. Despite an ever-growing amount of literature, research has remained fragmented. This comprehensive Handbook unites interdisciplinary scholarship, with contributions critically assessing the state and direction of behavioural public policies, their normative implications and political consequences.